Surface Emitting Semiconductor Laser Thermal and Radiation Analysis - Wang, Xiaodong (My University, 2013)
This paper discusses the topic of semiconductor laser, focused on two types of surface emitting laser: Vertical Cavity Surface Emitting Laser and Quantum Cascade Laser. The author analyzes the temperature profile in VCSEL with current injection and index change induced by thermal expansion. This result is useful for thermal lensing effects. For the Quantum Cascade Laser, the author investigates Eigenfrequency solver by commercial software to calculate the radiation loss for different type of grating and explain the trend of radiation loss as grating depth increases. Different types of grating influences are conducted later. There are also some graphs about calibration and measurement for etching and deposition of device. These are important parameters for future device fabrication. At last, the author suggests some future work in design and device fabrication.
Keywords: quantum cascade laser; vertical cavity surface emitting laser; surface emitting laser; semiconductor laser